2016
DOI: 10.21037/acs.2016.04.02
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between antegrade and retrograde cerebral perfusion or profound hypothermia as brain protection strategies during repair of type A aortic dissection

Abstract: Background: The goal of this study was to compare early postoperative outcomes and actuarial-free survival between patients who underwent repair of acute type A aortic dissection by the method of cerebral perfusion used.Methods: A total of 324 patients from five academic medical centers underwent repair of acute type A aortic dissection between January 2000 and December 2010. Of those, antegrade cerebral perfusion (ACP) was used for 84 patients, retrograde cerebral perfusion (RCP) was used for 55 patients, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…All 3 studies concluded that incidence of TND/PND and mortality was similar between the 2 cerebral protection adjuncts (TND, RCP 0-38% vs. ACP 1-34%; PND, RCP 1-9% vs. ACP 3-12%; mortality, RCP 3-6% vs. 2-4%). Retrospective studies composed of combined hemiarch and total arch replacement or limited to total arch replacement demonstrated similar results, with no significant difference between RCP and ACP regarding rates of mortality, TND, or PND as shown in the Table 1 (19,(23)(24)(25)(26)(27)(28). Of note, circulatory arrest time in recent reports is relatively short compared to decades ago, and this may have biased the difference between the 2 cerebral protection adjuncts.…”
Section: Comparison To Acpmentioning
confidence: 87%
“…All 3 studies concluded that incidence of TND/PND and mortality was similar between the 2 cerebral protection adjuncts (TND, RCP 0-38% vs. ACP 1-34%; PND, RCP 1-9% vs. ACP 3-12%; mortality, RCP 3-6% vs. 2-4%). Retrospective studies composed of combined hemiarch and total arch replacement or limited to total arch replacement demonstrated similar results, with no significant difference between RCP and ACP regarding rates of mortality, TND, or PND as shown in the Table 1 (19,(23)(24)(25)(26)(27)(28). Of note, circulatory arrest time in recent reports is relatively short compared to decades ago, and this may have biased the difference between the 2 cerebral protection adjuncts.…”
Section: Comparison To Acpmentioning
confidence: 87%
“…10 Using multivariable logistic regression, we found that independent predictors of operative mortality were hemodynamic instability and CPB time, not type of cerebral protection used. 10 The strongest negative effect of DHCA originates from increased CPB times and subsequent length of operation in comparison with MH. [11][12][13] Extended CPB times during cardiac surgery are implicated in increased risk of acute renal insufficiency, stroke, and mortality.…”
mentioning
confidence: 89%
“…These findings raise questions as to whether hypothermic temperature may also play a confounding role, as supported by a recent study by the senior author. 10 We compared survival between 324 patients undergoing AAAD repair with either DHCA, retrograde, or anterograde cerebral perfusion. 10 Using multivariable logistic regression, we found that independent predictors of operative mortality were hemodynamic instability and CPB time, not type of cerebral protection used.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Acute type A aortic dissection (ATAAD) is a life-threatening vascular emergency, mandating immediate surgical repair 1 . While developments in surgical, anaesthetic, and perfusion techniques have resulted in improved clinical outcomes, complex aortic arch procedures with hypothermic circulatory arrest (HCA), selective cerebral perfusion (SCP) and individual arterial cannulation modalities are still associated with a relatively high incidence of postoperative neurological complications and mortality 2 4 .…”
Section: Introductionmentioning
confidence: 99%